DAMPAK SOSIAL EKONOMI PADA KELUAGA TENAGA KERJA INDONESIA YANG BEKERJA DI LUAR NEGERI (STUDI KASUS TKI DI MALASIA) - IDA AYU KETUT MARINI; IDA BAGUS EKA ARTIKA; A.A. MADE SURYA KENCANA (GANEC SWARA, 2019)
Labor migration from one country to another or migration between countries in the era of globalization has become an increasingly easy phenomenon for workers, because of the various easy accesses that are supported by technology, increasingly supporting regulations and transportation to destenations which more expedite and more affordable.     This study aims to determine the social and economic impacts on Indonesian workers families (TKI) from Lombok Island who work in Malaysia. The sample of respondents is 70 families of migrant workers who were working in Malaysia, and interviews are conducted with the wives of the migrant workers. The results show that the families of migrant workers who work in Malaysia actually can improve the quality of social interaction, improve the education level of their children by prioritizing their children's schools, although the negative social impact is also felt by the wives of migrant workers working in Malaysia through Verbal abuse, nicknamed "Malaysian widow", seduced by other men, ostracized and made a rumor. Economically, families of migrant workers who work in Malaysia are able to improve the welfare of their families, even though all respondents go to Malaysia are stuck with capital debt, but after they get a salary, some of the salary sent to their wives is used to pay the debts, in addition to fulfilling other economic needs. To the regional government, especially the government of West Nusa Tenggara Province, considering that remittance produced by TKI who work abroad,hence a program is needed to improve the quality of workers who will be sent abroad through strengthening job training for prospective Indonesian workers who will be sent abroad